The COS CGM Compendium. V. The Dichotomy of O vi Associated with Low- and High-metallicity Cool Gas at z < 1 - Sameer; Nicolas Lehner; J. Christopher Howk; Andrew J. Fox; John M. O’Meara; Benjamin D. Oppenheimer (The Astrophysical Journal)
We analyze the O vi content and kinematics for 126 H i -selected absorbers at 0.14 ≲ z ≲ 0.73 for which the metallicities of their cool photoionized phase have been determined. We separate the absorbers into 100 strong Ly α forest systems (SLFSs with 15 ≲ log N (H i ) < 16.2) and 26 partial Lyman Limit systems (pLLSs with 16.2 ≤ log N (H i ) ≤ 17.2). The sample is drawn from the COS CGM Compendium (CCC) and has O vi coverage in signal-to-noise ratio ≥ 8 Hubble Space Telescope/COS G130M/G160M QSO spectra, yielding a 2 σ completeness level of $logN$ (O vi ) ≥ 13.6. The O vi detection rates differ substantially between low-metallicity (LM; [X/H] ≤ −1.4) and high-metallicity (HM; [X/H] > −1.4) SLFSs, with 20% and 60% detection rates, respectively. The O vi detection frequency for the HM and LM pLLSs is, however, similar at ∼60%. The SLFSs and pLLSs without detected O vi are consistent with the absorbing gas being in a single phase, while those with O vi trace multiphase gas. We show that the O vi velocity widths and column densities have different distributions in LM and HM gas. We find a strong correlation between O vi column density and metallicity. The strongest ( $logN$ (O vi ) ≳ 14) and broadest O vi absorbers are nearly always associated with HM absorbers, while weaker O vi absorbers are found in both LM and HM absorbers. From comparisons with galaxy-selected and blind O vi surveys, we conclude absorbers with $logN$ (O vi ) ≳ 14 most likely arise in the CGM of star-forming galaxies. Absorbers with weak O vi likely trace the extended CGM or intergalactic medium, while those without O vi likely originate in the intergalactic medium.